Preliminary Experience With Low Molecular Weight Heparin Strategy in COVID-19 Patients - Paolisso, Pasquale; Bergamaschi, Luca; D’Angelo, Emanuela Concetta; Donati, Francesco; Giannella, Maddalena; Tedeschi, Sara; Pascale, Renato; Bartoletti, Michele; Tesini, Giulia; Biffi, Mauro; Cosmi, Benilde; Pizzi, Carmine; et al. (Frontiers in Pharmacology, 2020)
Background Heparin administration in COVID-19 patients is recommended by expert consensus, although evidence about dosage, duration and efficacy are limited. We aim to investigate the association between different dosages of low molecular weight heparin (LMWH) and mortality among COVID-19 hospitalized patients. Methods and Results Retrospective study of 450 laboratory-confirmed COVID-19 patients admitted to Sant’Orsola Bologna Hospital from March 01 to April 10, 2020. Clinical, laboratory and treatment data were collected and analyzed. The in-hospital mortality between COVID-19 patients treated with standard prophylactic LMWH dosage vs intermediate LMWH dosage was compared. Out of 450 patients, 361 received standard deep vein thrombosis (DVT) prophylaxis enoxaparin treatment (40-60mg/Kg /day) and 89 patients received intermediate enoxaparin dosage (40-60 mg/Kg twice daily) for 7 days. No significant differences in the main demographic characteristics and laboratory testings at admission were observed in the two heparin regimen subgroups, except for older age and prevalence of hypertension in the group treated with “standard” prophylaxis LMWH dosage. The intermediate LMWH administration was associated with a lower in-hospital all-cause mortality compared to the “standard” prophylactic LMWH dosage (18.8% vs 5.8%, p = 0.02). This difference remained significant after adjustment with the propensity score for variables that differed significantly between the dosage groups (OR= 0.260, 95% CI 0.089 - 0.758, p=0.014). Conclusions Intermediate LMWH dosage seems to be associated with lower incidence of mortality compared to standard DVT prophylaxys in hospitalized COVID-19 patients. Our study paves the way to further pathophysiological investigations and controlled studies of anticoagulation therapy in Covid-19 disease.